Risk, wealth and agrarian change in India: household-level hazards vs. late-modern global risks at different points along the risk transition - Jewitt, Sarah; Baker, Kathleen (Elsevier, 2012)
The global poor often prioritise immediate hazards of food insecurity over temporally more distant risks like global warming. Yet the influence of socio-economic factors, temporal and spatial distance on risk perception remains under-researched. Data on risk perception and response were collected from two sets of Indian villages. Participatory approaches were used to investigate variations by socio-economic status, food security, age and gender. Villagers’ risk priorities reflected clear spatial and temporal patterns depending on land ownership, community group and education levels. Poorer groups prioritised household-level risks to health and food security while global environmental risks were mentioned by only three of the wealthiest respondents. The paper concludes that household risk perceptions and responses vary greatly with socio-economic status, age, gender and the spatial or temporal distance of the risk. These factors need to be better understood if the most significant contributors to the global burden of disease are to be reduced.